Characteristics of picky eater children in Turkey: a cross-sectional study - Suzan Yalcin; Ayse Oflu; Mustafa Akturfan; Siddika Songul Yalcin (BMC, 2022)
Abstract Objective The aim of this study is to investigate the relations of picky eating habit of children with their nutrition, physical activity, screen time and sleep habits in the context of parental picky eating habit. Methods In a cross-sectional study a questionnare was applied to the parents of children aged 6-13 years in two provincies. The cases were analyzed as the overall group and the two subgroups in which both parents are not picky eater, and in which at least one parent was picky eater. Child's risk of being picky eater was analyzed by logistic regression. Results A total of 913 children and parent pairs were included in the study. The risk of picky eating of the child increases 2.85 (AOR: 1.67-4.88) times when only the mother was picky eater, 5.99 (AOR: 3.32-7.52) times when only the father was picky eater, and 22.79 (AOR: 6.95-74.71) times when both of the parents were picky eaters. In the subgroup in which at least one parent was picky eater, it was determined that children with physical activity duration of ≥ 1 h/day and sleep time of ≥ 9 h /day were less likely to be picky eater and the children with screen time of ≥ 2 h/day were more likely to be picky eaters. Conclusion Picky eating habit in childhood is related to the picky eating habit of the parents. In the context of this relationship, the picky eating habit of children is related to sleep, physical activity, screen time and other eating habits.